Syncytiotrophoblast stress in early onset preeclampsia: The issues perpetuating the syndrome. (15th September 2021) - Carrasco-Wong, Ivo; Aguilera-Olguín, Macarena; Escalona-Rivano, Rodrigo; Chiarello, Delia I.; Barragán-Zúñiga, L. Jazel; Sosa-Macías, Martha; Galaviz-Hernandez, Carlos; San Martín, Sebastián; Gutiérrez, Jaime
Abstract: Preeclampsia is a pregnancy-specific syndrome characterized by a sudden increase in blood pressure accompanied by proteinuria and/or maternal multi-system damage associated to poor fetal outcome. In early-onset preeclampsia, utero-placental perfusion is altered, causing constant and progressive damage to the syncytiotrophoblast, generating syncytiotrophoblast stress. The latter leads to the detachment and release of syncytiotrophoblast fragments, anti-angiogenic factors and pro-inflammatory molecules into maternal circulation, resulting in the emergence and persistence of the characteristic symptoms of this syndrome during pregnancy. Therefore, understanding the origin and consequences of syncytiotrophoblast stress in preeclampsia is vital to develop new therapeutic alternatives, focused on reducing the burden of this syndrome. In this review, we describe five central characteristics of syncytial stress that should be targeted or prevented in order to reduce preeclampsia symptoms: histological alterations, syncytiotrophoblast damage, antiangiogenic protein export, placental deportation, and altered syncytiotrophoblast turnover. Therapeutic management of these characteristics may improve maternal and fetal outcomes. Graphical abstract: Image 1 Highlights: Syncytiotrophoblast stress drives the onset/persistence of preeclampsia symptoms. Stressed syncytiotrophoblast releases bioactive molecules to maternal circulation. In preeclampsia, syncytialization is reduced, thus perpetuating the symptoms.